Fabrication of novel ZrO2(Y2O3)–Al2O3 ceramics having high strength and toughness utilising pulsed electric current pressure sintering (PECPS). (February 2014) - Hirota, K.; Shibaya, K.; Matsuda, H.; Kato, M.; Taguchi, H.
Abstract : Pulsed electric current pressure sintering (PECPS) makes it possible to produce novel monolithic and composite materials with well controlled microstructure or nanostructure, which has not been realised before. ZrO2 based ceramics containing 25 mol.-%Al2 O3 and 0·90–1·125 mol.-%Y2 O3, i.e. ZrO2 (1·2–1·5 mol.-%Y2 O3 )–25 mol.-%Al2 O3, revealing high bending strength σ b ≧1 GPa and high fracture toughness K IC ≧15·5 MPa m 1/2 simultaneously, have been fabricated by PECPS of cubic ZrO2 solid solution (ss) powders containing both Al2 O3 and Y2 O3 prepared via a sol–gel process. Tetragonal ZrO2 ( t -ZrO2 ) phase composite ceramics sintered at 1573 to 1623 K (1300–1350°C) for 10 min under 60 MPa in Ar were composed of ∼ φ 200 nm grains with high relative density ≧97·5%. Transmission electron microscopy observation cleared that these mechanical properties might originate from homogeneous distribution of α -Al2 O3 particles in the dense t -ZrO2 matrix; the precipitation of α -Al2 O3 could be achieved by adopting the ss powders and PECPS.